As múltiplas faces do assédio moral no ensino superior privado na perspectiva de professores dos cursos de administração de empresas na cidade de São Paulo - Rodrigues, Míriam (2013)
This study has as its object the investigation of bullying from the perspective of teachers in courses of Business Administration of Higher Education Institutions (HEIs) private in São Paulo, with the aim to analyze the practice of bullying and conditions that organizational favor. To answer the question: ‘What organizational conditions favor occur and how the practices of bullying from the perspective of teachers of courses in Business Administration in private HEIs in São Paulo?’, a survey was conducted by a qualitative approach, guided by the interpretive paradigm, and the data collected through interviews and document analysis were subjected to content analysis. The results showed that bullying occurs in many instances, is motivated both by personal questions, as per organizational issues and has multiple faces, which manifest themselves in different forms of violence suffered by the teacher. The study contributes to the understanding of the practice of harassment in the academic environment, revealing that this phenomenon has as elements triggers the placement of private HEIs in the competitive landscape in which they operate and the weakness or absence of this rules and procedures relating to the prevention and treatment of cases of bullying.